2014
DOI: 10.1021/cr400525m
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Intrinsically Disordered Regions and Proteins

Abstract: Figure 1. Structured domains and intrinsically disordered regions (IDRs) are two fundamental classes of functional building blocks of proteins. The synergy between disordered regions and structured domains increases the functional versatility of proteins. Adapted with permission from ref 50.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

45
1,631
2
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,838 publications
(1,746 citation statements)
references
References 428 publications
(1,174 reference statements)
45
1,631
2
13
Order By: Relevance
“…First, one must show that the underlying binding reaction is entropy controlled, as determined by chain length, and second, that chain length times protein complex formation. Thus, a 'ball and chain' sequence functions as an entropic clock 14,25 . Addressing these requirements in the context of the Kv channel-PSD-95 interaction requires thermodynamics, kinetics and energetic information, none of which is yet available.…”
mentioning
confidence: 99%
“…First, one must show that the underlying binding reaction is entropy controlled, as determined by chain length, and second, that chain length times protein complex formation. Thus, a 'ball and chain' sequence functions as an entropic clock 14,25 . Addressing these requirements in the context of the Kv channel-PSD-95 interaction requires thermodynamics, kinetics and energetic information, none of which is yet available.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] As the eventual function of most (B80%) IDPs is to convey biological signals by binding to various types of target molecules, such as proteins, nucleic acids, metals, or lipids, 1,6,7 delineating their target-binding mechanism is important to clearly understand IDP function. Recent studies illustrate that accurate structural knowledge of IDPs may have immediate consequences even for drug development.…”
mentioning
confidence: 99%
“…Note that this question applies to B80% of IDPs. 7 Within this context the discovery of a PreSMo as an ''active site'' in the intrinsically disordered transactivation domain (TAD) of p53 was rather revealing since it demonstrated that local secondary structural elements in free IDPs could be the answer to the above question. 3,6 In fact, we now realize that IDPs are not total outliers completely defying the classical structure-function paradigm in the protein kingdom because IDPs use PreSMos to abide by the shape complementarity rule.…”
mentioning
confidence: 99%
“…The secondary structural elements of MAP_PRSO3010 and Rv0757 proteins were compared using PDBsum database [24]. The Position Specific Iterated Protein Secondary Structure Prediction server (PSIPRED) was employed to compare the transmembrane topology [25] and disorder regions [26] of Rv0757 and its orthologous protein from MAP.…”
Section:  Sequence Analysismentioning
confidence: 99%